EXAMINATION OF THE PRESENT CONDITION OF COMMODITY MARKETS WITHIN THE REALM OF FREIGHT RAIL TRANSPORTATION - Xusanova Nigora Patxullayevna; Mustayeva Guldora Salokhiddinovna (TADQIQOTLAR.UZ, 2024)
Abstract: This article engages in an exhaustive examination of the present conditions characterizing commodity markets within the sphere of freight rail transportation. By incorporating scholarly literature, delineating the selected research methodology, and rigorously analyzing the accumulated data, the study seeks to furnish meaningful insights into the contemporary dynamics and challenges within this domain. Additionally, it endeavors to present implications for stakeholders and make a substantive contribution to the extant scholarly knowledge in the field. Through this comprehensive approach, the article aims to enhance our understanding of the current state of commodity markets in freight rail transportation, shedding light on pertinent issues and considerations for industry participants, policymakers, and other stakeholders.